Tanggung Jawab Terhadap Pendidikan Anak: Analisis Kitab Tarbiyatul Aulad Fil Islam Karangan Abdullah Nashih Ulwan - rambe, sari madani rambe; Wahyudi, Hakmi (MGMP PAI SMP BINTAN, 2024)
The objective of this article is to explore comprehensively the obligations related to the education of children from the standpoint of Abdullah Nashih Ulwan as portrayed in his publication